Beating the odds : jump-starting developing countries - Lin, Justin Yifu; Monga, Célestin. (New Jersey ; Oxford, England : Princeton University Press, 2017)
The publication shows how poor countries can ignite growth without waiting for global action or the creation of ideal local conditions.
Includes index.
Includes bibliographical references p. 341-365.
ne 18/08/2022
Loans
Keywords: Economic development; Developing countries